Rise of the Eco-Comics: The State, Environmental Education and Canadian Comic Books, 1971-1975 - McLaughlin, Mark (Material Culture Review)

(untitled) (Cape Breton University Press, 2013)
Abstract In the 1960s and 1970s, North American governments used comic books with explicitly modern environmental themes or, as I have termed them, “eco-comics” as part of state-sponsored environmental education programs designed to mitigate the possible effects of the bourgeoning environmental movement on economic growth. This article contextualizes the eco-comic Captain Enviro (1972) within the post–Second World War anglophone Canadian comic book industry, discusses the emergence of environmental education in the 1960s and 1970s and uses a visual cultural analysis of Captain Enviro to unravel some of the nuances of the type of environmentalism advocated by the state—in this particular case, the Committee of Environment Ministers of the Council of Maritime Premiers—during this period.